Muscle-Enriched MicroRNAs Isolated from Whole Blood Are Regulated by Exercise and Are Potential Biomarkers of Cardiorespiratory Fitness - Denham, Joshua; Prestes, Priscilla R. (Frontiers in Genetics, 2016)
MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate gene expression post-transcriptionally. Evidence indicating miRNAs influence exercise-induced health and performance adaptations is mounting. Circulating miRNAs are responsible for intercellular communication and could serve as biomarkers for disease and exercise-related traits. Such biomarkers would contribute to exercise screening, monitoring, and the development of personalized exercise prescription. Accordingly, we investigated the impact of long-term strenuous aerobic exercise training and a single bout of maximal aerobic exercise on five muscle-enriched miRNAs implicated in exercise adaptations (miR-1, miR-133a, miR-181a, miR-486, and miR-494). We also determined linear correlations between miRNAs, resting heart rate, and maximum oxygen uptake (<inline-graphic xlink:href="fgene-07-00196-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2 max). We used TaqMan assay quantitative polymerase chain reaction to analyze the abundance of miR-1, miR-133a, miR-181a, miR-486, and miR-494 in resting whole blood of 67 endurance athletes and 61 healthy controls. Relative to controls, endurance athletes exhibited increased miR-1, miR-486, and miR-494 content (1.26- to 1.58-fold change, all p < 0.05). miR-1, miR-133a, and miR-486 were decreased immediately after maximal aerobic exercise (0.64- to 0.76-fold change, all p < 0.01) performed by 19 healthy, young men (20.7 ± 2.4 years). Finally, we observed positive correlations between miRNA abundance and <inline-graphic xlink:href="fgene-07-00196-i001.jpg" xmlns:xlink="http://www.w3.org/1999/xlink" />O2 max (miR-1 and miR-486) and an inverse correlation between miR-486 and resting heart rate. Therefore, muscle-enriched miRNAs isolated from whole blood are regulated by acute and long-term aerobic exercise training and could serve as biomarkers of cardiorespiratory fitness.